Predictors of HIV virological failure and drug resistance in Chinese patients after 48 months of antiretroviral treatment, 2008–2012: a prospective cohort study. Issue 9 (7th September 2017) - Kan, Wei; Teng, Tao; Liang, Shujia; Ma, Yanling; Tang, Heng; Zuohela, Tuerdi; Sun, Guoqing; He, Cui; Wall, Kristin M; Marconi, Vincent C; Liao, Lingjie; Leng, Xuebing; et al.
Abstract : Objective: To explore factors associated with HIV virological failure (VF) and HIV drug resistance (HIVDR) among HIV-positive Chinese individuals 4 years after initiating first-line lamivudine-based antiretroviral treatment (ART) in 2008 at five sentinel sites. Design: First-line ART initiators who were previously treatment naïve were selected using consecutive ID numbers from the 2008 National Surveillance Database into a prospective cohort study. Questionnaires and blood samples were collected in 2011 and 2012 to assess the outcomes of interest: VF (defined as viral load ≥1000 copies/mL) and HIVDR (defined as VF with genetic drug-resistant mutations). Questionnaires and data from National Surveillance Database assessed demographics and drug adherence data. Results: 536 individuals with HIV were analysed; the 4-year risk of VF was 63 (11.8%) and HIVDR was 27 (5.0%). Female participants initiating stavudine (D4T)-based regimens were more susceptible to both VF (adjusted OR (aOR)=2.5, 95% CI 1 to 6.1, p=0.04) and HIVDR (aOR=3.6, 95% CI 1 to 12.6, p=0.05) versus zidovudine-based regimens. Male participants missing doses in past month were more susceptible to both VF (aOR=2.8, 95% CI 1.1 to 7, p=0.03) and HIVDR (aOR=9.7, 95% CI 2.1 to 44.1, p<0.01). Participants of non-Han nationality were of increased risk for HIVDR (aOR from 4.8 to 12.2, p<0.05) and non-Han men were at increased risk for VF (aOR=2.9, 95% CI 1.1 to 7.3, p=0.02). All 27 participants detected with HIVDR had non-nucleoside reverse-transcriptase inhibitor mutations, 21 (77.8%) also had nucleoside reverse-transcriptase inhibitor mutations, and no protease inhibitor mutations were detected. Conclusions: Our findings suggest successful treatment outcomes at 4 years for roughly 90% of patients. We suggest conducting further study on whether and when to change ART regimen for women initiated with D4T-based regimen, and reinforcing adherence counselling for men. Increased VF and HIVDR risk among non-Han minorities warrants further exploration, and ethnic minorities may be an important group to tailor adherence-focused interventions.